2020
DOI: 10.1097/cad.0000000000000859
|View full text |Cite
|
Sign up to set email alerts
|

A case of pelvic giant cell tumor of bone, complete remission with denosumab: long duration of response

Abstract: Although giant cell tumor of bone has been considered as a disease with benign course, it can lead to bone destruction and serious morbidity. A 19-year-old case was presented with hip pain. There was a recurrence after 9 months of curative surgical resection and zoledronic acid use, and as surgical morbidity would be high, antiosteoclastic receptor activator of nuclear factor kappa B ligand inhibitor denosumab treatment was administered. She had a complete remission after 18 months of denosumab treatment. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A critical review of these published studies identified 60 studies that met the inclusion criteria for the present meta-analysis (Table 1). 11,12,44,60 -116 The www.clinicaltrials.gov website showed 7 ongoing studies of denosumab in the treatment of GCTB. The majority of the studies examined for this meta-analysis were case reports, case series studies, and nonrandomized, uncontrolled, open-label phase II studies (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A critical review of these published studies identified 60 studies that met the inclusion criteria for the present meta-analysis (Table 1). 11,12,44,60 -116 The www.clinicaltrials.gov website showed 7 ongoing studies of denosumab in the treatment of GCTB. The majority of the studies examined for this meta-analysis were case reports, case series studies, and nonrandomized, uncontrolled, open-label phase II studies (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Most participants in the studies analyzed were from case series studies, followed by the nonrandomized, uncontrolled, openlabel phase II studies, and then case reports. 90 Tsukamoto et al 92 Matcuk et al 106 Bilgetekin et al 62 Xará-Leite et al 65 Marinova et al 68 Kinoshita et al 70 Osaka et al 71 Liu et al 74 Wu et al 84 Law et al 85 Satcher et al 87 Yonezawa et al 89 Bardakhchyan et al 91 (continued) Menon et al 95 Inoue et al 97 Cavalcante et al 99 Yamagishi et al 100 Kajiwara et al 101 Nakazawa et al Setsu et al 103 Aponte-Tinao et al 104 Park et al 105 Vaishya et al 107 Gossai et al 109 Watanabe et al 110 Mattei et al 111 Hakozaki et al 112 Aghaloo et al 113 Rossi et al 114 Akaike Abbreviation: SD, standard deviation a The majority of study participants were women, and the median age was 30. There was no significant difference in the duration of treatment and follow-up time.…”
Section: Proportion Of Participants In Each Study Design Typementioning
confidence: 99%
See 1 more Smart Citation
“…Although the occasional use of ZA as a salvage treatment in DM non-responders has been reported [50] , the position of ZA in the treatment of GCTB next to DM remains unexplored. The reverse sequence has been studied, but ZA was most often ineffective as a first-line option, while DM allowed for long-term disease control [51] , [52] , [53] .…”
Section: Discussionmentioning
confidence: 99%